Preliminary experience of combined dual plasma molecular adsorption system and plasma exchange in pediatric acute liver failure: a retrospective case series - Jia-Hao Geng; Shi-Lin Liu; Bao-Fan Dou; Jun-Lin Zhao; He-Kai Ma; Zhi-Yuan Wang; Shu-Jun Li (BMC Pediatrics)
Abstract Background Pediatric acute liver failure (PALF) is a life-threatening condition with no definitive treatment. This study evaluated the combined use of the dual plasma molecular adsorption system (DPMAS) and plasma exchange (PE) to improve liver function and survival outcomes in PALF patients. Methods A retrospective study was conducted on 7 PALF patients treated with DPMAS and PE. Data on liver function scores (Liver Injury Unit [LIU], Model for End-Stage Liver Disease [MELD], Model for End-Stage Liver Disease with Sodium [MELD-Na], MELD 3.0), bilirubin levels, and coagulation indices were collected before and after treatment. Results DPMAS and PE treatments significantly reduced total bilirubin (382.2 µmol/L to 52.0 µmol/L) and improved coagulation indices. Liver injury scores decreased notably (e.g., LIU from 184 to 52 in one case). Five patients recovered, while two with severe comorbidities showed limited improvement. Conclusion The combination of DPMAS and PE therapy improves liver function and survival outcomes in PALF. These results support its use as a bridge to recovery or transplantation in PALF patients, though further studies with larger sample sizes are needed.